2016
DOI: 10.1371/journal.pone.0149180
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation Reduces Induction of Epithelial-Mesenchymal Transition in Allergen Sensitized and Challenged Mice

Abstract: Asthma is a chronic disease of the lung associated with airway hyperresponsiveness (AHR), airway obstruction and airway remodeling. Airway remodeling involves differentiation of airway epithelial cells into myofibroblasts via epithelial-mesenchymal transition (EMT) to intensify the degree of subepithelial fibrosis. EMT involves loss in E-cadherin with an increase in mesenchymal markers, including vimentin and N-cadherin. There is growing evidence that vitamin D has immunomodulatory and anti-inflammatory proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 44 publications
2
32
0
1
Order By: Relevance
“…Further examination of the airways in mice that were fed a diet supplemented with 10,000 IU/kg of vitamin D showed increased expression of E-cadherin and decreased expression of vimentin and N-cadherin in airway epithelial cells. 20 …”
Section: Results From Animal Studiesmentioning
confidence: 99%
“…Further examination of the airways in mice that were fed a diet supplemented with 10,000 IU/kg of vitamin D showed increased expression of E-cadherin and decreased expression of vimentin and N-cadherin in airway epithelial cells. 20 …”
Section: Results From Animal Studiesmentioning
confidence: 99%
“…In murine models, vitamin D deficiency is associated with airway hyper-responsiveness (AHR), as well as with increased pro-inflammatory cytokines and reduced T-regulatory (T-reg) cells in bronchoalveolar lavage fluid (BALF) 33 . Moreover, vitamin D supplementation attenuates allergen-induced inflammation and AHR in sensitized mice 33,34 . Among children, three common genetic variants in the class I MHC–restricted T cell–associated molecule gene (CRTAM) have been associated with asthma exacerbations in those with vitamin D deficiency 35 , and polymorphisms in the gene for the vitamin D receptor have been associated with asthma 365 .…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of dietary factors have the capacity to alter epithelial behavior via direct receptor action or indirect regulation of tissue metabolism. For example, Fischer et al demonstrated that vitamin D supplementation, acting via the vitamin D receptor pathway, reduces EMT processes and improves barrier function in several clinically relevant murine models of asthma 89 . Fatty acid-deficient diets spontaneously induce skin barrier disruption via alteration of skin metabolism 90, 91 .…”
Section: Mechanisms Of Barrier Defectsmentioning
confidence: 99%